2020
DOI: 10.5194/acp-20-2319-2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of NU-WRF model performance on air quality simulation under various model resolutions – an investigation within the framework of MICS-Asia Phase III

Abstract: Abstract. Horizontal grid resolution has a profound effect on model performances on meteorology and air quality simulations. In contribution to MICS-Asia Phase III, one of whose goals was to identify and reduce model uncertainty in air quality prediction, this study examined the impact of grid resolution on meteorology and air quality simulation over East Asia, focusing on the North China Plain (NCP) region. The NASA Unified Weather Research and Forecasting (NU-WRF) model has been applied with the horizontal r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…(3) The direct aerosol radiative effect dominated the feedback effect in this study, so more cases in different regions and seasons, when the indirect effect could be more important, are needed to elucidate the complete feedback mechanism at different spatial and temporal scales. (4) Finer model grid resolution is expected to be applied to look into details of the feedback effect at the urban scale along with finer-resolution emission inventories (Tao et al, 2020), vertical observations (Wilcox et al, 2016;Wang et al, 2018), and higher computational efficiency when available in the future. Finally, this study pointed out the significance and necessity of developing online coupled models for exploring chemistry-aerosol-weather-climate interactions and for improving meteorological and chemical predictions in both air quality and climate research in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The direct aerosol radiative effect dominated the feedback effect in this study, so more cases in different regions and seasons, when the indirect effect could be more important, are needed to elucidate the complete feedback mechanism at different spatial and temporal scales. (4) Finer model grid resolution is expected to be applied to look into details of the feedback effect at the urban scale along with finer-resolution emission inventories (Tao et al, 2020), vertical observations (Wilcox et al, 2016;Wang et al, 2018), and higher computational efficiency when available in the future. Finally, this study pointed out the significance and necessity of developing online coupled models for exploring chemistry-aerosol-weather-climate interactions and for improving meteorological and chemical predictions in both air quality and climate research in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Aerosols affect radiation transfer by scattering or absorbing solar and infrared radiation, by acting as cloud condensation nuclei (CCN) to modify cloud properties, and by heating the atmosphere to alter cloud formation, termed as the aerosol direct radiative effect, indirect effect, and semi-direct effect, respectively (Twomey, 1974;Albrecht, 1989;Ramanathan et al, 2001). In addition, there exists a set of interactions between chemistry, radiation, and meteorology (Dawson et al, 2007;Zhang, 2008;Isaksen et al, 2009;Baklanov et al, 2014;Cai et al, 2017), which is highly complex and nonlinear, and this is currently one of the least understood mechanisms in the atmospheric science community.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity simulation also requires expensive computational resources, which results in most global simulations of pollutants running at coarse horizontal resolutions ranging from 1 • × 1 • to 5 • × 5 • , such as 4 • × 5 • in J. , 2 • × 2.5 • in Han et al (2020), 1 • × 1 • in Crippa et al (2019), and 2.8 • × 2.8 • in Nagashima et al (2017), and S-R relationships are limited to a few regions (e.g., Europe, North America, East Asia, South Asia). Many recent studies have revealed that horizontal resolution has a considerable influence on model performance in air quality simulations (Lin et al, 2010;Tao et al, 2020). Urban-scale pollution plumes are often unresolved in global model simulations with lower resolution, which tend to underestimate the magnitude of pollution formation and destruction, especially in urban areas (Huijnen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity simulation also requires expensive computational resources, which results in most global simulations of pollutants running at coarse horizontal resolutions ranging from 1°×1° to 5°×5° , such as 4°×5° in Zhu et al (2017a), 2°×2.5° in Han et al (2020), 1°×1° in Crippa et al (2019), and 2.8°×2.8° in Nagashima et al (2017), and S-R relationships are limited to a few regions (e.g., Europe, North America, East Asia, South Asia). Many recent studies have revealed that horizontal resolution has a considerable influence on model performance in air quality simulations (Lin et al, 2010;Tao et al, 2020). Urban-scale pollution plumes are often unresolved in global model simulations with lower resolution, which tend to underestimate the magnitude of pollution formation and destruction, especially in urban areas (Huijnen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%